2009
DOI: 10.1177/1350506808101761
|View full text |Cite
|
Sign up to set email alerts
|

Virginal Facades

Abstract: Charged with personal, societal and legal significance, the hymen, as a fold of flesh, has the power to rule the sexual identities of unmarried women in Turkey. This article examines the forms and associated meanings of contemporary challenges to virginity rules among educationally advantaged, upwardly mobile young women. The article demonstrates that in the process of negotiating often contradictory expectations of their sexual behavior, young women cultivate purposefully ambiguous identities related to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Turkey and Morocco differ markedly when it comes to the timing of union formation. This is the case despite the countries' common heritage of a 'culture of honour and shame' (Peristiany 1965) that makes women's premarital virginity a matter of the family's reputation (Parla 2001;Ozyegin 2009) and despite the fact that marriage is practically universal. According to the 2003 Turkish Demographic and Health Survey, the median age of first-time marriage among women aged 25-29 was 21, while for women aged 45-49 it was nineteen; this indicates a two-year increase occurred over twenty years.…”
Section: Transition To First Unionmentioning
confidence: 99%
“…Turkey and Morocco differ markedly when it comes to the timing of union formation. This is the case despite the countries' common heritage of a 'culture of honour and shame' (Peristiany 1965) that makes women's premarital virginity a matter of the family's reputation (Parla 2001;Ozyegin 2009) and despite the fact that marriage is practically universal. According to the 2003 Turkish Demographic and Health Survey, the median age of first-time marriage among women aged 25-29 was 21, while for women aged 45-49 it was nineteen; this indicates a two-year increase occurred over twenty years.…”
Section: Transition To First Unionmentioning
confidence: 99%
“…A study examining the initial sexual intercourse experiences of women found that perceived sexual coercion and control of the partner are associated with more physical pain during intercourse and less sexual satisfaction (Wang & Ho, 2011). In addition, young, highly educated, and unmarried individuals, especially those with sexually conservative parents, report problems with enjoying sexual intercourse because they perceive it as a betrayal to their parents (zyegin, 2009). From the SDT perspective, perceived parental sexual control may limit the fulfillment of emerging adults' autonomy, competence, and relatedness needs and have adverse implications for youth's sexual well‐being.…”
Section: Self‐determination Theory Perceived Parental Control and Eme...mentioning
confidence: 99%
“…Yet Turkish families maintain gender hierarchy (where men's roles are providing for the family and protecting its dignity, and women's role is dedicating themselves to the care of family members) and generational hierarchy (parents over children; Bolak‐Boratav et al, 2017; Parla et al, 2001) in family structure and continue to condemn premarital sex, especially for single adult women (Özyegin, 2009). In addition, most Turkish emerging adults reside with their parents until they marry (Turkey Statistical Institute, 2020), and only 2.8% of the general population live with roommates.…”
Section: Perceived Parental Control and Well‐being Of Emerging Adults...mentioning
confidence: 99%
“…Since the 1980s, rapid and pervasive cultural and economic change has shaken the fixity of national, class, religious, gender, and sexual identities in Turkey. The premarital sexual relationship between male and female youth is still a strict taboo, and the virginity of girls is still highly praised in Turkish society (Ozyegin, 2009). The society idealizes female chastity and the symbolic value of virginity as an indicator of honor and purity for females that relates to the honor of family, parents, and the nation in an order (Cindoglu, 1997).…”
Section: Limitationsmentioning
confidence: 99%